A case report of a cystic fibrosis patient with repeated isolation of Trichosporon mycotoxinivorans identified by a novel short-extraction method. Issue 1 (December 2016) - Goldenberger, Daniel; Hinić, Vladimira; Prince, Spasenija; Tamm, Michael; Balestra, Anna-Maria; Hohler, Doris; Frei, Reno
Abstract Background Trichosporon mycotoxinivorans is a recently described yeast-like fungal organism and its association as a pathogen for patients with cystic fibrosis (CF) was reported previously. We show the clinical course of a CF patient over 9 years as well as the applications of modern molecular and proteomic identification techniques of this rare fungus. Case presentation We present the case of a 32-year-old male CF patient with sputum cultures continuously positive with the anamorphic yeastT. mycotoxinivorans during 9 years. Furthermore, susceptibility testing ofT. mycotoxinivorans to different antifungals were performed. In addition, a rapid identification method of this novel fungal pathogen with matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) was applied using a simple extraction protocol. Conclusions Our case presentation confirmsT. mycotoxinivorans as a potential emerging pathogen in patients with CF. However, our CF patient showed mild symptoms over a very long time period of 9 years. A short MALDI-TOF MS procedure allows reliable and rapid identification ofT. mycotoxinivorans and therefore should facilitate further study on the clinical relevance and epidemiology of this unusual fungal organism.